INSCRIPTION RELATED TO THE PALLICHANDAM GRANTED BY THE PANDIAS IN THE 13TH CENTURY (International Journal of Food and Nutritional Sciences, 2022)
The Pandiyas of the Sangam and the early Pandiyas donated lands and jewels to various temples. The later Pandayas also continued this tradition and donated lands, prestigious Jewels to the temples. The donations given to the temples as land were known as Palli chandam. The early Pandayas and the Cholas constructed innumerable Saivite and Vaishnavite temples throughout the Tamil country. For the better administration of the temple and the local governance, the kings rendered many endowments, i.e cash, jewels, lands, etc. During the period of the second Pandya empire, the kings continued and carried out religious work with pious towards god. They imprinted the details of the donations in inscriptions. This article highlights such an inscription of the second Pandya reign discovered at Vadakkunatham village in Virudhunagar district.